Examining Bachelor of Science in Nursing Accelerated (BSNA) Program Outcomes within a Traditional Faculty Workload Model versus a Clock Hour Faculty Workload Model. - Blackard, Glynis D. (Examining Bachelor of Science in Nursing Accelerated (BSNA) Program Outcomes Within a Traditional Faculty Workload Model Versus a Clock Hour Faculty Workload Mod, 2016)
Literature evaluating the impact of faculty workload on student outcomes of graduation and first-time pass for the National Council on Licensure Examination (NCLEX-RNRTM) is limited. Current models of workload are not specific and do not define the number of hours the faculty spends doing the work. In this day of decreased funding and increased requirement for quality in academia, it is important for nurse educators to understand how quality program outcomes, finances, and faculty workload are connected and impact student involvement. The purpose of this study was to examine the relationship between the program outcomes of graduation and first-time pass on the National Council on Licensure Examination -- Registered Nurse (NCLEX-RNRTM) for Bachelor of Science Nursing Accelerated (BSNA) student graduates in programs that used a traditional faculty workload model versus a clock hour faculty workload model. The study, though limited, did begin to evaluate the impact of faculty workload on program outcomes. The intent and goals of the study were to research traditional workload models and alternative models proposed to address the cost of education and establish a baseline of how the models may impact program outcomes. In addition, the intent included evaluating how future changes may ultimately impact the student. Implications of the study included the consideration by faculty, school of nursing administration, and university administration of how faculty workload impacts the classroom and practice environment. Recommendations for further research conclude the study.